TRAPPED: TECHNOLOGY AS A BARRIER TO LEAVING AN ABUSIVE RELATIONSHIP. - HALLIGAN, CAITLIN; KNOX, DAVID; BRINKLEY, JASON (College Student Journal)
A 42 item Internet questionnaire was completed by 259 undergraduates at a large southeastern university designed to assess the degree to which individuals involved in abusive relationships would report that technology in the form of text messages, email, and Facebook would impair their ability to terminate the relationship. Almost sixty percent respondents (regardless of their demographic background or whether they were in an abusive relationship) reported frequent use of technology. However, respondents needing to leave an abusive relationship more frequently identified with those areas that would be perceived as a barrier (e.g. receiving text messages that called the respondent names). And, those who were "abuse prone" were more likely to stay in abusive relationships even though parents and friends disapproved. Implications and limitations are identified.